The Tax Law of Private Foundations, 5th Edition - Hopkins, Bruce; Blazek, Jody (Wiley, 2020)
The Tax Law of Private Foundations: 2020 Cumulative Supplement, 5th Edition.
Online resource; Title from title page (viewed November 3, 2020)